Tlingit grave box on shore of Portlock's Harbor, Portlock Alaska, in engraving made 1787 - Woodcock, J.
Photograph of engraving of harbor; two men in small boat in water near small islands. On shore near grove of trees is a burial box raised on stilts Caption on image: View in Portlock's Harbour, NE [sic] Coast of America. Publish'd June 17, 1789, by J. Stockdale & G. Goulding